A comprehensive insight into the effects of microbial spoilage, myoglobin autoxidation, lipid oxidation, and protein oxidation on the discoloration of rabbit meat during retail display. (February 2021) - Wang, Zhaoming; Tu, Juncai; Zhou, Hui; Lu, An; Xu, Baocai
Abstract: The effects of the retail display temperature (8 °C, 3 °C and − 1 °C) on the discoloration of the Longissimus thoracis et lumborum of rabbits and the associations among such effects with microbial spoilage, myoglobin autoxidation, lipid oxidation, and protein oxidation were investigated. The total aerobic count, total volatile basic nitrogen content, metmyoglobin content, protein carbonyl content, and contents of thiobarbituric acid-reactive substances steadily increased during retail display. Moreover, the lightness and redness of the rabbit meat significantly ( P <  0.05) declined over time, whereas the yellowness increased considerably ( P <  0.05) with prolonged retail time. Canonical correlation analysis suggested that microbial spoilage, myoglobin autoxidation, lipid oxidation, and protein oxidation jointly affected rabbit meat color. Linear mixed models further revealed that microbial spoilage, myoglobin autoxidation, lipid oxidation and protein oxidation positively affected yellowness, and they inversely impacted lightness and redness. Highlights: The effects of retail display temperatures (8°C, 3 °C and -1 °C) on the discoloration of rabbit meat were investigated. Linear mixed models were used to estimate the relationship between color changes versus microbial spoilage and oxidation reactions. Rabbit meat color was affected by myoglobin autoxidation, microbial spoilage, lipid oxidation, and protein oxidation during retail display. -1 °C can be developed as a commercial retail temperature for rabbit meat.